U-236, Np-237 and Pu-239,Pu-240 as complementary fingerprints of radioactive effluents in the western Mediterranean Sea and in the Canada Basin (Arctic Ocean) - López Lora, Mercedes; Chamizo, Elena; Levy, Isabelle; Christl, Marcus; Casacuberta, Nuria; Kenna, Timothy C. (Science of The Total Environment, 2021)
The aim of this study was to assess the potential of combining the conservatively behaving anthropogenic radionuclides U-236 and Np-237 to gain information on the origin of water masses tagged with liquid effluents from Nuclear Reprocessing Plants. This work includes samples collected from three full-depth water columns in two areas: i) the Arctic Ocean, where Atlantic waters carry the signal of Sellafield (United Kingdom) and La Hague (France) nuclear reprocessing facilities; and ii) the western Mediterranean Sea, directly impacted by Marcoule reprocessing plant (France). This work is complemented by the study of the particle-reactive Pu isotopes as an additional fingerprint of the source region. In the Canada Basin, Atlantic waters showed the highest concentrations and Np-237/U-236 ratios in agreement with the estimated values for North Atlantic waters entering the Arctic Ocean and tagged with the signal of European Nuclear Reprocessing Plants. These results may reflect the impact of the documented releases for the 1990s. In the Mediterranean Sea, an excess of U-236 presumably caused by Marcoule is reflected in the lower Np-237/U-236 ratios compared to the Global Fallout signal in all the studied samples. On the contrary, the Pu-239,Pu-240 profiles were mainly governed by the Global Fallout. The impact of Marcoule as a local source is further corroborated when comparing the temporal evolution of these ratios between 2001 and 2013. The lowest Np-237/U-236 ratios observed in 2001 at the surface reflect a previous local input that is no longer observed in 2013 as it had been homogenized through the whole water column. This work presents the use of Np-237 as a new ocean tracer. A more accurate characterization of the main sources is still needed to optimize the use of U-236-Np-237 as a new tool to understand transient oceanographic processes. (C) 2020 Elsevier B.V. All rights reserved. Funding Agencies|Spanish Government (Ministerio de Economia y Competitividad) [FIS2015-69673-P, PGC2018-094546-B-I00]; Spanish ...